Deformation of graphene on an oxidizing nickel surface: the role of graphene layer number. (16th November 2016) - George, Lijin; Shaina, P R; Gupta, Aparna; Das Gupta, Nandita; Jaiswal, Manu
Abstract: Few-layer graphene grown on nickel substrates by chemical vapour deposition is typically characterised by thickness inhomogeneity. In this work, we investigate the thickness-dependent changes induced in graphene during the surface oxidation of the underlying metal. Temperature-dependent Raman spectroscopy and scanning electron microscopy are used to monitor the lattice strain and defect formation induced in graphene, as well as the oxidation of Ni surface. Significant lattice strain is induced in thin layers of graphene (1–2 layers) during the oxidation process, for T  > 400 °C. This is followed by the formation of boundary-type defects, and graphene loses structural integrity. In contrast, lattice strain induced in thicker graphene (up to 7 layers) during the metal surface oxidation is quite subdued. These thicker layers de-pin and remain structurally intact even after the underneath metal surface has oxidized.